Breaststroke Swimming Learning Model Based on Virtual Reality: A Quasi-Experimental Study on College Students - Raswin Raswin; Afri Tantri; Doris Apriani Ritonga; Muhammad Ishak; Muhammad Yan Ahady; Muhammad Reza Destya (Journal Coaching Education Sports, 2026)
This study aims to assess the effectiveness of a virtual reality-based breaststroke learning model on improving students' swimming skills. The background of this study is based on the limitations of conventional learning methods in visualizing swimming technique movements in detail, resulting in low understanding of movement and quality of students' motor skills. The study used a quasi-experimental design with a pretest-posttest control group pattern. The research subjects consisted of physical education students who were divided into an experimental group (using virtual reality media) and a control group (using conventional learning). The research instrument was a breaststroke swimming skills test that covered aspects of body position, arm movement, leg movement, breathing, and motor coordination. Data were analyzed using statistical tests to compare the improvement in learning outcomes of the two groups. The results showed that the group that participated in virtual reality-based learning experienced a significantly higher improvement in breaststroke swimming skills compared to the conventional learning group. These findings indicate that the integration of virtual reality technology in swimming learning can improve movement understanding, the quality of technique execution, and student learning motivation. Thus, a virtual reality-based learning model is recommended as an innovative alternative in swimming learning in higher education.